Presence of Heterobasidion annosum and the need for stump treatment in monocultures of Scots pine in southern Sweden - Petrylaitė, Eglė (SLU/Southern Swedish Forest Research Centre, 2004)
The incidence of Heterobasidion spp. in the roots of Scots pine (Pinus sylvestris L.) was investigated in fifteen monocultures of Scots pine in southern Sweden. On the basis of crown condition, all trees were divided into four classes from healthy to dead trees on a number of sample plots at each site. The root systems were excavated and sample discs were taken from two healthy looking trees and two defoliated trees in each stand. All samples were analysed for the presence of Heterobasidion spp. The data was used to create a probability model for trees getting infected. Estimated volume losses were then compared to the costs for treating stumps. Heterobasidion spp. was found in root samples from pines at fourteen of the fifteen stands. A total of 44 of the 60 sampled trees were infected by Heterobasidion spp. in the root systems. Of the infected pines 20 trees were assessed as healthy looking and 24 as defoliated trees. Previous land use, thinning season and crown condition class had significant effects on the percentage of root discs infected by Heterobasidion spp. Accordingly, highest probability of finding an infected tree was among the defoliated trees in stands on former agricultural land with thinnings carried out during season of spore spread. The results show that at three percent interest rate stump treatment to prevent spore infection of Heterobasidion spp. in monocultures of Scots pine in southern Sweden is clearly beneficial, especially in stands established on former arable land.